Written Zimbabwean drama as/ and intervention: The case of Raisedon Baya's Super Patriots and Morons and Tomorrow's People - Vhutuza, Ephraim (2016)
The paper discusses written Zimbabwean drama as/and intervention. Using the theory of scenarios and anti-scenarios, the paper focuses on Raisedon Baya's two dramas: Super Patriots and Morons and Tomorrow's People written in 2001 and 2004 respectively. Both plays were finally published as an anthology of plays entitled Tomorrow's People and Other Plays in 2009 with a grant from the Culture Fund and Sida. The paper argues that written drama like institutions such as theatre, the church, local and international civic bodies and supranational identities such as SADC,AU, EU, UN among others, can be used successfully to plead with those in power on behalf of ordinary citizens for certain structural changes to be made in a given society. This advocacy role is inevitable in written Zimbabwean drama famously known for engaging with immediate issues affecting society; in the process challenging the dominant ideology as part of the broad coalition of oppositional cultural and or ideological actors. Such drama assumes a prominent role in the troubled, diseased and choking Zimbabwean landscape of 2001-2004 when the plays were written. Interventionist drama is one of multiple possibilities and the paper attempts to demonstrate how Raisedon Baya's drama has 'intervened' in a country saddled with violence, suspicion, tribal hatred, political intolerance and other social, economic and political ills.